Perceptions of intolerant norms both facilitate and inhibit collective action among sexual minorities. (October 2022) - Eisner, Léïla; Settersten, Richard; Turner-Zwinkels, Felicity; Hässler, Tabea
This article presents the results of three studies that examine how the perceived opinions of others are related to sexual minorities' support for social change toward greater equality. Results of two cross-sectional studies (Study 1: N = 1, 220; Study 2: N = 904) reveal that perceived intolerance (i.e., perceived intolerant societal norms) is indirectly related to intentions to engage in collective action in both negative and positive ways: the negative effect was mediated by lower perceptions of perceived efficacy; positive effects were mediated by greater anger (about the legal situation and public opinion) and greater perceived need for a movement. Study 3 ( N = 408) replicates this conflicting effect with a delayed outcome measure by showing that perceived intolerant norms were indirectly, both negatively and positively, associated with actual collective action engagement. We discuss the theoretical and practical implications of our expanded social identity model of collective action.